2005
DOI: 10.1262/jrd.17039
|View full text |Cite
|
Sign up to set email alerts
|

Expression Patterns of the Implantation-associated Genes in the Uterus during the Estrous Cycle in Mice

Abstract: Abstract. The mRNA expression patterns of EGF, HB-EGF, Amphiregulin, EGF receptor, IGF-1, CSF-1, IL-1 alpha, IL-1 beta, IL-1 receptor type 1, IL-1 receptor antagonist, LIF, COX-1, COX-2, Mucin-1, calcitonin, and rat USAG-1 mouse homologue, all of which are involved in the process of conceptus implantation to the endometrium, were examined during the estrous cycle by means of real-time quantitative PCR. COX-2, HB-EGF, LIF, Mucin-1, CSF-1, IL-1 alpha, IL-1 beta, and IL-1 receptor antagonist were temporally regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 57 publications
0
17
0
Order By: Relevance
“…GAPDH was used as a reference control to normalize the loading of template cDNA. The sequences of each pair of primers were as follows: HB-EGF forward: 59-TCCGTCTGTCTTCTTGTCATCGT-39, HB-EGF reverse: 59-TAGCCACGCCCAACTTCACT-39; EGF forward: 59-CCAAACGCGAAGACTTATCC-39, EGF reverse: 59-TGATCCTCAAA-CACGGCTAGAGA-39; TGF-a forward: 59-GCCCAGATTCCCACACT CAGTA-39, TGF-a reverse: 59-TCTGCATGCTCACAGCGAA-39; EGFR forward: 59-CATCTGTGCCCAGCAATGTT-39, EGFR reverse: 59-TTGC-ATGTGGCCTCATCTTG-39; and GAPDH forward: 59-TGCATCCTGCA-CCACCAACTGCTTAG-39, GAPDH reverse: 59-GGCATGGACTGTGGT-CATGA-39 (20,21). …”
Section: Quantitative Real-time Pcrmentioning
confidence: 99%
“…GAPDH was used as a reference control to normalize the loading of template cDNA. The sequences of each pair of primers were as follows: HB-EGF forward: 59-TCCGTCTGTCTTCTTGTCATCGT-39, HB-EGF reverse: 59-TAGCCACGCCCAACTTCACT-39; EGF forward: 59-CCAAACGCGAAGACTTATCC-39, EGF reverse: 59-TGATCCTCAAA-CACGGCTAGAGA-39; TGF-a forward: 59-GCCCAGATTCCCACACT CAGTA-39, TGF-a reverse: 59-TCTGCATGCTCACAGCGAA-39; EGFR forward: 59-CATCTGTGCCCAGCAATGTT-39, EGFR reverse: 59-TTGC-ATGTGGCCTCATCTTG-39; and GAPDH forward: 59-TGCATCCTGCA-CCACCAACTGCTTAG-39, GAPDH reverse: 59-GGCATGGACTGTGGT-CATGA-39 (20,21). …”
Section: Quantitative Real-time Pcrmentioning
confidence: 99%
“…On the other hand, it has been shown that amphiregulin mRNA is expressed throughout the e s t r o u s c y c l e i n t h e m o u s e u t e r u s [ 1 4 ] . Furthermore, the highest expression level of amphiregulin during diestrus is not consistent with the LIF mRNA expression pattern during the estrous cycle [14]. As shown in Fig.…”
Section: Discussionmentioning
confidence: 67%
“…The gene expression rate was obtained by normalizing the amount of amphiregulin cDNA with that of beta-actin. Total RNA from the oviducts and uteri of nonpregnant a n i m a l s w e r e u s e d a s c o n t r o l s b e c a u s e amphiregulin mRNA is stably expressed during the estrous cycle [14].…”
Section: Real-time Quantitative Pcrmentioning
confidence: 99%
“…The homology of rat USAG-1 cDNA to those of mouse and human is 96% and 91%, respectively [7]. W e p r e v i o u s l y i d e n t i f i e d U S A G -1 m R N A expression in mouse uteri during the estrous cycle [8]. In contrast to the temporally regulated expressions of COX-1, COX-2, EGF, LIF, and other growth factors/cytokines, USAG-1 mRNA expression did not change during the estrous cycle [8].…”
mentioning
confidence: 99%
“…W e p r e v i o u s l y i d e n t i f i e d U S A G -1 m R N A expression in mouse uteri during the estrous cycle [8]. In contrast to the temporally regulated expressions of COX-1, COX-2, EGF, LIF, and other growth factors/cytokines, USAG-1 mRNA expression did not change during the estrous cycle [8]. However, the expression pattern and function of USAG-1 in the mouse uterus during the periimplantation period have not been studied.…”
mentioning
confidence: 99%